Jurnalistik: Antara Jurnalisme dan idealisme - Rewira, Andi Edwin (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2024)
This study examines the discourse between journalism and idealism in media practice. The issue arises from the challenge journalists face in balancing objectivity and social responsibility with external pressures such as political, economic, and industry interests. The aim of this research is to analyze how journalists navigate the tension between professional demands and their idealistic aspirations for the media's societal role. A qualitative approach was employed, utilizing case study analysis and media experts. Findings reveal that while a gap exists between idealism and journalistic practice, journalists develop strategies to maintain editorial integrity. This study highlights the need for greater awareness of press freedom and journalistic ethics to preserve the quality of information.